Clinic-Laboratory Classification of Primary Minor Immunodeficiencies in Humans - Dmytro, Maltsev (Trends in Immunotherapy, 2025)
Only some primary immunodeficiencies are often found in the population, characterized by a mild clinical phenotype and creating a significant burden on society, so-called primary minor immunodeficiencies (PMD). The study aims to create a clinical and laboratory classification of PMD in humans for basic science and practical medicine. A systematic review of scientific publications in PubMed (MEDLINE) from 1980 to 2025 was conducted using keywords through a sequential two-stage search. The terminology has been clarified and an original clinical and laboratory classification of PMD in humans has been developed according to the following rubrics: origin, affected immune factor, immune system branch and form of immunity, family history, time of debut, frequency in the population, genetic nature, clinical picture, depth of immune factor damage, severity of the patient’s condition, duration of the immunological phenotype, evolutionary development scenario, regularity of manifestations, involvement of local and systemic immunity, combinations with each other and with other diseases, curability and some special headings. The significance of the developed classification for fundamental science and clinical practice has been clarified, and promising directions for further research to improve the proposed classification have been indicated. The introduction of a classification will demonstrate the diversity of PMD in humans, enabling both improved clinical diagnosis in individuals with associated immune-dependent pathology and a contribution to the intensification and optimization of clinical research.